Media Personnel Identity Crisis - Al LeBlanc (The Canadian Network for Innovation in Education (CNIE), 1986)
One of the greatest stress points for media personnel is the problem of role perception by fellow employees within an institution and from outside the field. To compound the problem is a lack of clear definition of duties and functions from the general to the specific. Very often the question, "What do you do for a living?" generates a puzzled expression as we try to put into layperson's terms what it is that we do (so well).